Back Cover: Exchange bias at low fields exhibited by the interface between epitaxial layers of ferromagnetic and charge‐ordered rare‐earth manganites (Phys. Status Solidi RRL 8/2016). Issue 8 (August 2016) - Saha, Rana; Vasu, K.; Negi, D. S.; Datta, R.; Sundaresan, A.; Rao, C. N. R.
Abstract : No abstract is available for this article. Abstract : The back cover depicts epitaxial bilayers of charge‐ordered antiferromagnetic Y0.5 Ca0.5 MnO3 (YCMO) and ferromagnetic La0.7 Sr0.3 MnO3 (LSMO), deposited on SrTiO3 (STO) substrate. Significant exchange bias is observed in the heterostructures even in the presence of a very small cooling magnetic field ( 5 Oe), cf. the Letter by R. Saha, C. N. R. Rao and coworkers (pp.622–626 ). The unidirectional exchange anisotropy at the interface can be switched by reversing the polarity of the cooling magnetic field. The observation of exchange bias in LSMO–YCMO bilayers in the presence of a small magnetic field provides a means to control exchange‐coupled interfaces in the heterostructures. The occurrence of exchange bias at the oxide interface upon cooling in a small magnetic field in the presence of strong biaxial strain imposed by STO opens venues to study the physics of the orbital‐ordered state and the interfacial spin configuration of charge‐orbital‐ordered manganites. Furthermore, this observation would help to design new oxide heterostructures with better functionality which would be useful for spintronics and related electronic devices.